Fundamental pathways in breast cancer 3: Estrogen biology - Magnani,L; Patten,DK (2017)
Over the last two decades, it has become evident that breast cancer should be considered as a family of diseases rather than as a unique malignancy. Pathological, molecular, and genetic analysis have revealed the existence of five to ten main subgroups [1-3]. Over 70% of all patients are generally classified by the tumor dependencies on estrogenic compounds [4]. These dependencies are principally mediated by the nuclear receptor estrogen receptor a (ERa) [5, 6]. For all these reasons, ERa remains the key driver in the majority of breast cancers and is commonly used as a molecular biomarker for stratification while serving as the main target for systemic adjuvant chemotherapy. In this chapter I will discuss the molecular mechanisms of ERa activation focusing on integrative analysis that have recently exposed the intimate link between ERa and chromatin structure.